Strength and Bearing Capacity of Rectangular Footing Rested on a Soil Layer Reinforced with Waste Materials - Abood, Mazin J.; Shakir, Ressol R. (Basrah Journal for Engineering Sciences, 2025)
A series of unconfined compression and direct shear tests were carried out to investigate the compressive strength and shear strength parameters of clay soil reinforced with different contents and lengths of wheat straw and palm frond fibers and by adding different percentages of furnace slag. The bearing capacity and settlement characteristics of the rectangular footing based on a clay soil layer reinforced with wheat straw fibers, palm fronds and furnace slag at different thicknesses were also studied by conducting model footing tests. The results indicated that the compressive strength and shear strength parameters improved significantly when adding 0.5% of natural fibers and 20% of furnace slag. The maximum compressive strength of soil samples reinforced with wheat straw fiber MT1 and palm frond fiber MT2 was 365 and 407 kPa, respectively. Compared to the unreinforced sample, samples reinforced with natural fibers and furnace slag significantly improve the shear strength parameters c and ϕ . The cohesion of soil sample reinforced with wheat straw and palm frond fibers increased by 8% and 43% respectively, while the internal friction angles improved by 19% and 40% respectively. The sample treated with furnace slag MT3 showed improved significantly in cohesion by 76% and less effect in internal friction angle. Compared to unreinforced soil samples, the cohesion of soil samples reinforced with wheat straw and palm fibers and treated with furnace slag MT4 and MT5 increased by 77% and 92% respectively, and less effect in internal friction angle. Moreover, the bearing capacity and settlement characteristics of the rectangular footing improved significantly with the increase in the thickness of the top layer reinforced with natural fibers and treated with furnace slag. The ultimate bearing capacity of layer reinforced with wheat straw fibers MT1 increases to 193.2, 220.15 and 247.5 kPa at thicknesses of 0.5 B, 1.0 B, and 1.5 B respectively, while the settlement decreased by 10.4%, 15% and 20.48% respectively at same thicknesses.